2019
DOI: 10.1016/j.aap.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Analysing truck harsh braking incidents to study roundabout accident risk

Abstract: In order to reduce accident risk, highway authorities prioritise maintenance budgets partly based upon previous accident history. However, as accident rates have continued to fall, this approach has become problematic as accident 'black spots' have been treated and the number of accidents at any individual site has fallen, making previous accident history a less reliable indicator of future accident risk. Another way of identifying sites of higher accident risk might be to identify near-miss accidents (where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In this study, fps is 60, and α h = 10.648 mph/s chosen according to [16]. The number of brakes and harsh brakes can be counted respectively using {B j }.…”
Section: The Number Of Brakesmentioning
confidence: 99%
“…In this study, fps is 60, and α h = 10.648 mph/s chosen according to [16]. The number of brakes and harsh brakes can be counted respectively using {B j }.…”
Section: The Number Of Brakesmentioning
confidence: 99%
“…There is consensus that driving within the acceleration values of ±0.05g is considered steady state driving (Ozaki 1993;Ali et al 2019). However, various studies have used different thresholds for classifying harsh acceleration events (Kamla, Parry, and Dawson 2019). A threshold of around 0.5g has often been used in transportation studies to classify harsh braking and lateral accelerations events.…”
Section: Comparing the Influence Various Fixed Effectsmentioning
confidence: 99%
“…The positive correlation between crash and harsh acceleration rates has been shown for both longitudinal as well as lateral acceleration events (Simons-Morton et al 2012). However, when trying to explore these correlations, varied acceleration thresholds have been used to define harsh acceleration events and a consistent methodology does not exist (Kamla, Parry, and Dawson 2019). Moreover, most studies analyzing harsh acceleration events do not simultaneously control for the various factors that could be affecting driver acceleration behavior such as roadway properties, driver demographics, vehicle characteristics, and environmental features.…”
Section: Introductionmentioning
confidence: 99%
“…Using simulated driving environments, hard-braking by distracted motorists was found to have significant impacts on following vehicles in traffic, increasing the risk of a rear-end collision (Haque and Washington 2015). Investigations into the use of harsh braking incidents as a surrogate for truck crash counts using truck telematics data have shown promise in identifying potential hot spots with high crash risk (Kamla et al 2019). A 6-month study of drivers in Georgia traveling on freeways, arterials, and local roads found that those involved in a crash incident tend to more frequently hard brake (8.8 ft/s 2 ) than those not involved in crashes (Jun et al 2007).…”
Section: Literature Reviewmentioning
confidence: 99%